Permeabilitas Tanah Lanau Sebagai Temporary Landfill Cover yang Distabilisasi dengan Bakteri dan Larutan Sementasi - Alfian Rahmadi; Andi Marini Indriani; Gunaedy Utomo (Kadiri University, 2023)
In the development of waste management, piles of rubbish can produce liquid waste called leachate. Leachate from landfills can affect human health and pollute the environment and aquatic biota because leachate contains various chemical compounds and many pathogenic bacteria. To minimize the impact of landfill waste on the surrounding environment, the waste is covered with material that can isolate it from the surrounding environment. This research aims to determine the optimal level of cementation solution addition to waste sludge as temporary landfill cover using the MICP method. The research results reveal that the sample permeability meets the criteria for a temporary cover landfill, where the permeability specification limits are between 10-4 to 10-5 cm/s. The research revealed that 0.25M cementation solution and Bacillus Subtilis bacteria had the lowest permeability. Soil without cementation solution has a permeability coefficient value of 5.04×10-4 cm/s, and decreases to 6.67×10-5 cm/s with a cementation solution concentration of 0.25M over a 28-day peram period. Variations in the 0.25M cementation solution showed its ability to reduce soil permeability by up to 86.7%. Permeability has decreased, which means the soil pores are getting smaller. Thus, this addition can reduce soil permeability and minimize the possibility of environmental damage by leachate.